Implementation of the Quran Memorization Curriculum in Developing Student Character at MIS Humayroh, Parpaudangan Village, North Labuhanbatu - Aziz, Mursal; Napitupulu, Dedi Sahputra; Lubis, Robi’atul Hafizoh (-, 2025)
This study aims to analyze the implementation of the Tahfizhul Qur'an Curriculum in developing students' characters at the Humayroh Private Elementary School (MIS), Parpaudangan Village, North Labuhanbatu. The Tahfizhul Qur'an Curriculum is one of the educational approaches that teaching and memorizing the Qur'an as an integral part of the process of forming students' characters. This study uses a qualitative approach with a case study method to obtain an in-depth picture of the implementation of this curriculum. Data were collected through observation, interviews with teachers, students, and principals, and related documentation. The results of the study indicate that the implementation of the Tahfizhul Qur'an curriculum at MIS Humayroh not only focuses on the memorization aspect of the Qur'an, but also on strengthening moral and spiritual values, such as discipline, responsibility, and respect for others. This curriculum has a positive impact on the development of students' characters, where they show improvements in terms of morals, social skills, and learning motivation. However, there are challenges in terms of educator resources and facilities that need to be improved to support optimal performance implementation. This study recommends improving training for teachers and providing more adequate facilities so that the goal of character development through Tahfizhul Qur'an can be achieved more effectively.